Measurement of forward charged hadron flow harmonics in peripheral PbPb collisions at √𝑠𝑁⁢𝑁=5.02TeV with the LHCb detector - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Cocha Toapaxi, Carlos; De Cian, Michel; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Herrero Gascón, Paula; Langenbruch, Christoph; Leverington, Blake; Marks, Jörg; et al. (Physical review, 2024)
Flow harmonic coefficients, 𝑣𝑛, which are the key to studying the hydrodynamics of the quark-gluon plasma (QGP) created in heavy-ion collisions, have been measured in various collision systems and kinematic regions and using various particle species. The study of flow harmonics in a wide pseudorapidity range is particularly valuable to understand the temperature dependence of the shear viscosity to entropy density ratio of the QGP. This paper presents the first LHCb results of the second- and the third-order flow harmonic coefficients of charged hadrons as a function of transverse momentum in the forward region, corresponding to pseudorapidities between 2.0 and 4.9, using the data collected from PbPb collisions in 2018 at a center-of-mass energy of 5.02 TeV. The coefficients measured using the two-particle angular correlation analysis method are smaller than the central-pseudorapidity measurements at ALICE and ATLAS from the same collision system but share similar features.